2013
DOI: 10.1177/1477153513491760
|View full text |Cite
|
Sign up to set email alerts
|

Subjective evaluation of luminance distribution for intelligent outdoor lighting

Abstract: A large number of physical dimensions and different criteria make choosing the optimal luminance distribution for outdoor lighting difficult. The optimisation becomes even more complex for light-emitting diode-based lighting installations that can be intelligently operated, providing different luminance distributions around a moving traffic participant. This study aims at establishing the main subjective factors for the assessment of the luminance distribution of an intelligent light-emitting diode-based outdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Additionally, the study covered a relatively large number of observation points (257), in 10 different neighborhoods, in three different cities-all of which contribute to higher generality. It should also be noted that previous studies involved relatively small numbers of research subjects, and evaluated relatively small numbers of lighting sources, thus, falling short of representing different urban settings, larger populations and population subgroups [1,29,33,57]. The present study effectively addresses these drawbacks and may lead the way for future studies to be conducted elsewhere.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
“…Additionally, the study covered a relatively large number of observation points (257), in 10 different neighborhoods, in three different cities-all of which contribute to higher generality. It should also be noted that previous studies involved relatively small numbers of research subjects, and evaluated relatively small numbers of lighting sources, thus, falling short of representing different urban settings, larger populations and population subgroups [1,29,33,57]. The present study effectively addresses these drawbacks and may lead the way for future studies to be conducted elsewhere.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
“…There is some evidence that distributing light to highlight natural objects rather than artificial objects enhances reassurance. 65,66 Finally, two studies demonstrate that spatial distribution needs to consider the location of the pedestrian, 63,64 for example, a possible preference for brighter lighting in the immediate vicinity of a pedestrian, and thus the need for dynamic control over spatial distribution. Spatial distribution is the least wellinvestigated characteristic: there is a need to repeat past studies to extend and confirm the findings, and to consider how the lighting designer might respond to these issues.…”
Section: Resultsmentioning
confidence: 99%
“…The results from three studies [63][64][65] indicate that alternative approaches to spatial distribution should be considered. Haans and de Kort 63 compared three variations of spatial distribution using a row of five luminaires ( Figure 6): Conventional (all set to the same light output), ascending (low light level at observation point, increasing light level further away) and descending (high light level at observation point, decreasing light level further away), with all three designed to provide the same overall amount of light.…”
Section: Spatial Distribution Of Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al 10 found no effect of the number of sources on discomfort glare either; they used a vertical panel of LEDs to simulate road lighting in the laboratory. Pedestrian studies also suggest that observers feel the discomfort glare due to one luminaire at a time 5 , and judge the lighting quality with respect to the luminaire closest to them 11 .…”
Section: Contextmentioning
confidence: 99%